On the Edge of Dispensability, the Chloroplast ndh Genes - Bartolomé Sabater (MDPI AG, 2021)
The polypeptides encoded by the chloroplast ndh genes and some nuclear genes form the thylakoid NADH dehydrogenase (Ndh) complex, homologous to the mitochondrial complex I. Except for Charophyceae (algae related to higher plants) and a few Prasinophyceae, all eukaryotic algae lack ndh genes. Among vascular plants, the ndh genes are absent in epiphytic and in some species scattered among different genera, families, and orders. The recent identification of many plants lacking plastid ndh genes allows comparison on phylogenetic trees and functional investigations of the ndh genes. The ndh genes protect Angiosperms under various terrestrial stresses, maintaining efficient photosynthesis. On the edge of dispensability, ndh genes provide a test for the natural selection of photosynthesis-related genes in evolution. Variable evolutionary environments place Angiosperms without ndh genes at risk of extinction and, probably, most extant ones may have lost ndh genes recently. Therefore, they are evolutionary endpoints in phylogenetic trees. The low number of sequenced plastid DNA and the long lifespan of some Gymnosperms lacking ndh genes challenge models about the role of ndh genes protecting against stress and promoting leaf senescence. Additional DNA sequencing in Gymnosperms and investigations into the molecular mechanisms of their response to stress will provide a unified model of the evolutionary and functional consequences of the lack of ndh genes.